Evaluation of stone mastic asphalt mix by the Bailey method design - Chou, X.; Chegenizadeh, Amin; Nikraz, Hamid (Australian Geomechanics Journal, 2016)
A series of wheel tracking tests are performed in this study. Mixtures are designed based on a designer's experience and grading curves developed from past practice. This has led to many issues with inconsistent and poor performing SMA on the focus of rutting resistance. An investigation to evaluate the Bailey Method as a tool for designing SMA mix built on aggregate packing was undertaken. The Bailey Method was used to design a SMA blend which was then manufactured, tested and compared against conventional SMA used in Western Australia. Results show that the degree of aggregate packing directly influences the rutting resistance performance of Stone Mastic Asphalt using similar aggregates. The Bailey Method provided a useful tool in improving the behaviour of aggregate packing characteristics within SMA.